Football brand managers perspectives how to deal with fans emotions - Cayolla, R. R.; Loureiro, S. M. C. (Academia Letters, 2021)
Football brand managers are part of the sport industry. With structured in-depth personal interviews to seven of the top half Portuguese football clubs, our aim is to have a deeper knowledge about the professional perspective, strategies and actions to attract fans and maintain their relationship with the club (i.e. brand). Negativity effect, fan identity, and memory are the three major themes that emerged and also discussed in the light of known literature.